Incorporating Cooperative Learning to Enhance University Students’ Speaking Ability in English - Sarala Thulasi Palpanadan; Nur Amirah Shapie; Nurul Hidayah Maderon; Nurulhamizah Sami`'An; Muhammad Syafiq Iqmal Ismail; Muhammad Zainuddin Yuslee (Development in Language Studies, 2022)
Cooperative learning involves an educational approach that encourages socializing and learning among students of all levels including preschool, primary and secondary schools, and tertiary education across all topic areas. Students take part in cooperative learning to attain a common objective or finish a group activity by communicating with each other. Many studies were conducted that clearly highlighted that cooperative learning can be utilized to increase reading and writing accomplishment, conceptual growth in science, problem-solving in mathematics, and higher-level thinking and reasoning. Thus, this study was conducted to investigate the university students’ perceptions regarding incorporating cooperative learning to enhance their speaking ability in English. A total of 112 final-year students who had enrolled in a language course at the university participated in a survey conducted. The data was analyzed using SPSS where the mean scores were derived. The findings showed that most of the students responded positively regarding the implementation of cooperative learning. The mean scores ranged between 3.30 (speaking confidence) and 3.69 (enhancing teamwork spirit). Thus, the study recommends the practice of the cooperative learning method is used more profoundly in educational settings especially to enhance the speaking skills of English for university students.